The Effect of Product Quality and Service Quality on Consumer Loyalty at Palopo Minimarkets - Fasiha, Fasiha; Yusuf, Muhammad; Sihombing, Humiras Betty Marlina; Mujahidin, Mujahidin; Chenini, Rachid (Universitas Islam Negeri Raden Intan Lampung, 2022)
This research discusses Consumer Implications of Minimarkets' Product and Service Quality Loyalty. This study's primary objective is to determine influence of product quality and service quality on consumer commitment. The type of research used is quantitative research with the research population of all minimarket consumers with sampling techniques using non-probability sampling, the saturated sample technique (census). Data collected using questionnaires were analyzed using multiple regression analysis and for processing data using SPSS version 22. The results of this study showed that the product quality variable (X1) was obtained by the calculated t value > t table (3.822 > 2.012) or a significance value of 0.000 < 0.05 and the service quality variable (X2) of the calculated t value > t table (3.329 > 2.012) or a significance value of 0.02 <0.05. So it can be concluded that product quality and service quality have a positive effect on consumer loyalty.